The role of interleukin-22 in lung health and its therapeutic potential for COVID-19 - Fang, Si; Ju, Dianwen; Lin, Yong; Chen, Wei (Frontiers in Immunology, 2022)
Although numerous clinical trials have been implemented, an absolutely effective treatment against coronavirus disease 2019 (COVID-19) is still elusive. Interleukin-22 (IL-22) has attracted great interest over recent years, making it one of the best-studied cytokines of the interleukin-10 (IL-10) family. Unlike most interleukins, the major impact of IL-22 is exclusively on fibroblasts and epithelial cells due to the restricted expression of receptor. Numerous studies have suggested that IL-22 plays a crucial role in anti-viral infections through significantly ameliorating the immune cell-mediated inflammatory responses, and reducing tissue injury as well as further promoting epithelial repair and regeneration. Herein, we pay special attention to the role of IL-22 in the lungs. We summarize the latest progress in our understanding of IL-22 in lung health and disease and further discuss maneuvering this cytokine as potential immunotherapeutic strategy for the effective manage of COVID-19.